Exploring Ideologically Diverse Friend Groups Among College Students at a Christian University - Patterson, Sarah E. (Christian higher education, 2024)
Ideological diversity, or the “honest consideration of multiple views, often competing for claims that privileges a vigorous or spirited debate of ideologically different ideas which are to be judged on their logical soundness and intellectual merit” (Von Bergen & Bressler, 2017, p. 26), is a growing research interest in the higher education field in recent years. However, minimal research has explored ideological diversity within peer interactions and friend groups, or within the Christian college setting. This exploratory, qualitative, symbolic interactionist study therefore sought to address the following research questions: (1) How do college students at a Christian university develop and maintain ideologically diverse friend groups? and (2) What are the perceived outcomes of such friendships? Findings from interviews with 11 undergraduate students from shared friend groups at a single Christian university revealed how college students become members of ideologically diverse friend groups (IDFGs), how students engaged in conflict within such friend groups, and whether students in IDFGs can influence the student experience in a manner that promotes the field’s aspirations for holistic education (Chambliss & Takacs, 2014; Denson et al., 2017). Our analysis ultimately affirms that IDFGs are meaningful for student development and the overall student experience. Consequently, we conclude this article by providing insights for how Christian higher education professionals might support initiatives and spaces that promote IDFGs on their own campuses.